New Prospects for Particle Characterization Using Analytical Centrifugation with Sector-Shaped Centerpieces - Uttinger, Maximilian; Boldt, Sebastian; Wawra, Simon; Freiwald, Tobias; Damm, Cornelia; Walter, Johannes; Lerche, Dietmar; Peukert, Wolfgang (Particle & Particle Systems Characterization, 2020)
Analytical centrifugation (AC) has recently shown great potential for the accurate determination of particle size distributions. The well-established LUMiSizer(R) is customized by a new design allowing for higher rotor speeds, improved thermal insulation, and measurement cell assembly. The latter enables sedimentation analysis of nanoparticles (NPs) in sector-shaped centerpieces. The measurement window of AC experiments is assessed by the Peclet (Pe) number. It is shown that at low Pe numbers (0.7 < Pe < 30), sedimentation, and diffusion can be accurately and simultaneously analyzed from the sedimentation boundaries within one experiment. Moreover, sedimentation properties can be reliably determined up to Pe numbers of 4000. The thermal characteristic throughout the sedimentation analysis is validated by measuring polystyrene particles at elevated temperatures. Moreover, the performance of the setup is demonstrated by determining the sedimentation properties of SiO2 NPs at intermediate Pe numbers in excellent agreement with results from analytical ultracentrifugation experiments. Finally, for the first time, an accurate analysis of the core–shell properties of Au NPs via AC is presented. By combining the analysis of sedimentation and diffusional properties at low Pe numbers, the shell thickness of the stabilizer cetyltrimethylammonium bromide alongside the core diameter distribution of the Au NPs is determined.
CRIS-Team Scopus Importer:2020-06-19
Keywords: analytical centrifugation; core–shell nanoparticles; layering effects; nanoparticle characterization; sedimentation analysis